Sangay volcano (Ecuador): the opening of two new vents, a drumbeat seismic sequence and a new lava flow in late 2021 - Hidalgo, Silvana; Vasconez, Francisco Javier; Battaglia, Jean; Bernard, Benjamin; Espín, Pedro; Valade, Sébastien; Naranjo, María-Fernanda; Campion, Robin; Salgado, Josué; Córdova, Marco; Almeida, Marco; Hernández, Stephen; et al. (Volcanica, 2022)
On 2 December, 2021 we recorded a sequence of drumbeat seismic events at Sangay volcano. This sequence lasted several hours and resulted in two explosive emissions whose eruptive columns reached 9 km above crater. Unexpectedly, these explosions did not produce any ash fallout in the inhabited areas around the volcano. This drumbeat sequence was produced after a series of morphological changes, including the opening of two new vents (W and N) and a landslide. These occurred during an enhanced period of ground deformation and degassing. Further analysis of satellite images allowed us to determine that this sequence was associated with the widening of the recently open vent north of the main crater, and the extrusion of a new lava flow. Timely communication of this event to the authorities and the population was ensured by the IG-EPN by following internal protocols. The corresponding short reports reached more than 300,000 people.